RETRACTED: Cultural foundations of the educational system and legal upbringing in the conditions of contemporary political and legal reality transformation - Rybak Svetlana; Krygina Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001